The Effect of Positivism Training on Rumination, Body Image and Sexual Satisfaction in Women with Recurrent Pregnancy Loss - Azadeh Falsafi; Zahra DashtBozorgi (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: One of the major stressors for families, especially women, is a recurrent pregnancy loss that exposes them to many psychological problems. This research aimed to investigate the effectiveness of positivism training on rumination, body image and sexual satisfaction in women with recurrent pregnancy loss. Methods: This was a semi-experimental research with a pre-test and post-test design and an experimental and control group. Research population was women with recurrent pregnancy loss referring to Imam Khomeini (Rah) and Razi hospitals in Ahvaz city in spring of 2018. Sample research was 40 people that were selected by available sampling method and assigned into two equal groups. The experimental group was trained for 8 sessions of 90 minutes with positivism method and the control group didn't receive any training. The groups completed the questionnaires of rumination, body image and sexual satisfaction in the pre-test and post-test stages. Data was analyzed by multivariate analysis of covariance method using SPSS 19. Results: The findings showed that there was a significant difference between the experimental and control groups in terms of rumination, body image and sexual satisfaction. In the other words, positivism training led to a decrease in rumination and positive body image and sexual satisfaction in women with recurrent pregnancy loss (P<0/001). Conclusion: The results indicated the effect of positivism training in improving rumination, body image and sexual satisfaction in women with recurrent pregnancy loss. Therefore, counselors and therapists can use positivism training to intervention in the field of rumination, body image and sexual satisfaction.